Microvascular Assessment of Ranolazine in Non-Obstructive Atherosclerosis: The MARINA Randomized, Double-Blinded, Controlled Pilot Trial. (December 2020) - Koh, Jin-Sin; Hung, Olivia Y.; Eshtehardi, Parham; Kumar, Arnav; Rabah, Rani; Raad, Mohamad; Kumar, Sonali; Chaudhry, Sundeep; Gupta, Sonu; Hosseini, Hossein; Brilakis, Emmanouil; Corban, Michel; et al.
Abstract : Background: Microvascular dysfunction is known to play a key role in patients with angina and nonobstructive coronary artery disease. We investigated the impact of ranolazine among patients with angina and nonobstructive coronary artery disease. Methods: In this randomized, double-blinded, placebo-controlled pilot trial, 26 patients with angina once weekly or more, abnormal stress test, and nonobstructive coronary artery disease (<50% stenosis by angiography and fractional flow reserve >0.80) were randomized 1:1 to ranolazine or placebo for 12 weeks. Primary end point was ΔSeattle Angina Questionnaire (SAQ) angina frequency score. Baseline and 3 months follow-up SAQ, Duke Activity Status Index scores along with invasive fractional flow reserve, coronary flow reserve (CFR), hyperemic myocardial resistance, and cardiopulmonary exercise testing measurements were performed. Results: No significant differences in ΔSAQ angina frequency scores ( P =0.53) or Duke Activity Status Index ( P =0.76) were observed between ranolazine versus placebo, although patients on ranolazine had lesser improvement in SAQ physical limitation scores ( P =0.02) compared with placebo at 3 months. There were no significant differences in ΔCFR or Δhyperemic myocardial resistance between ranolazine and placebo groups. Patients treated with ranolazine, compared with placebo, had no significant improvement in maximum rate of oxygen consumption measured during incremental exercise (VO2 max) and peak metabolic equivalents of task. Interestingly, in the ranolazine group, patients with baseline CFR<2.0 demonstrated greater gain in CFR compared with those with baseline CFR≥2.0 ( P =0.02). Conclusions: Ranolazine did not demonstrate improvement in SAQ angina frequency score, invasive microvascular function, or peak metabolic equivalent compared with placebo at 3 months. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02147067. Abstract : Supplemental Digital Content is available in the text.